Stakeholder management and project management office: effect on project results - Rabechini, Roque Jr. (2022)
Managing stakeholders is relevant for project management, as they affect project results. Likewise, the support of a Project Management Office (PMO) improves these results. This study analyzes the positive influence of stakeholder management on project results, specifically on the likelihood of concluding projects within the predicted time and cost, together with the moderating effect of PMOs. A conceptual model was validated through logistic regression, with data collected through a survey responded by 216 experienced professionals studying in graduate programs on project management. Findings indicate that stakeholder management improves project results in terms of time and cost and confirm that PMO enhances the influence of stakeholder management on these results. As its contribution, the study reinforces stakeholder management and PMO as key elements for successful project management. Sampling was sufficient for research replicability but restricted to professionals of project management living in Peru. Thus, future studies could target a broader population.